The Effect of Company Size, Credit Risk, and Capital Ratio On Stock Prices With Corporate Social Responsibility As A Moderating Variable In Banking Companies On The Indonesia Stock Exchange (International Journal of Scientific Research and Management (IJSRM), 2025)
This study explores the factors influencing stock prices of banking companies on the Indonesia Stock Exchange (IDX), focusing on firm size, credit risk (NPL), and capital ratio (DER/CAR), as well as the role of Corporate Social Responsibility (CSR) as a moderating variable. Using a sample of 220 observations from 47 banks listed on the IDX for the 2020–2022 period, Partial Least Squares (PLS) analysis revealed three key findings. First, firm size had a positive and significant impact on stock prices, demonstrating that investors place greater confidence in banks with substantial assets due to their stability and scalability. Second, credit risk (NPL) showed a negative but insignificant effect, suggesting that investors may be less sensitive to this factor in investment decisions. Third, the capital ratio had a positive and significant effect, confirming that capital adequacy signals trust to the market. Interestingly, CSR was shown to strengthen the relationship between these three variables and stock prices, suggesting that sustainability practices not only enhance reputation but also magnify the impact of fundamental factors on stock valuation. These findings provide valuable insights for investors in assessing the prospects of banking investments, while also emphasizing the importance of integrating CSR as a business strategy that is not only ethical but also enhances market appeal. Consequently, regulators and industry players can leverage these findings to promote more transparent and sustainable policies and practices.